Immunoprofile of the adenomatoid odontogenic tumor - Reichart P. (2017)
© 2016 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd This study was focused on the immunohistochemical profile of the adenomatoid odontogenic tumor. A Pub/Medline search revealed a number of immunohistochemical studies including cytokeratin profiles, extracellular matrix proteins, Integrins, ameloblast-associated proteins resorption regulators (RANK, RANKL), p53, PCNA, MDM2 protein, cyclin D1, Ki-67, Bcl-2 metallothionein, metalloproteinases, D56 hepatocyte growth factor, c-met, DNA methyltransferase, podoplanin, TGF-βI, Smad-2/3, Smad-I-5/-8, Smad 4, beta- catenin, calretinin, and clonality. Careful interpretation of the findings indicates that the adenomatoid odontogenic tumor may be more of a hamartomatous than neoplastic nature.